The impact of lymph node metastases and right hemicolectomy on outcomes in appendiceal neuroendocrine tumours (aNETs). Issue 6 (June 2021) - Alabraba, Edward; Pritchard, David Mark; Griffin, Rebecca; Diaz-Nieto, Rafael; Banks, Melissa; Cuthbertson, Daniel James; Fenwick, Stephen
A bstract: Introduction: European Neuroendocrine Tumour Society (ENETS) recommends managing appendiceal neuroendocrine tumours (aNET) with appendicectomy and possibly completion right hemicolectomy (CRH). However, disease behaviour and survival patterns remain uncertain. Materials and methods: We retrospectively assessed the impact of lymph nodes and CRH on outcomes, including survival, in all aNET patients diagnosed between 1990 and 2016. Results: 102 patients (52F, 50 M), median age 39.4 (range 16.3–81.1) years, were diagnosed with aNET. Mean tumour size was 12.7 (range 1–60) mm, most sited in appendiceal tip (63%). Index surgery was appendicectomy in 79% of cases while the remainder underwent colectomy. CRH performed in 30 patients at a median 3.2 (range 1.4–9.8) months post-index surgery yielded residual disease in nine: lymph nodes (n = 8) or residual tumour (n = 1). Univariate logistic regression showed residual disease was significantly predicted by tumour size ≥2 cm (p = 0.020). Four patients declined CRH, but did not suffer relapse or reduced survival. One patient developed recurrence after 16.5 years of follow-up and another patient developed a second neuroendocrine tumour after 18.8 years follow-up. There were 5 deaths; one being aNET-related. 5-year and 10-year overall survival were 99% and 92% respectively; 5-year and 10-year relapse-free survival were 98% and 92% respectively. Only 5-year relapse-free survival was affected by ENETS stage (p = 0.002). Conclusion: aNETs are indolent with very high rates of overall and relapse-free survival. Recurrence is rare, and in this series only occurred decades later, making a compelling case for selective surveillance and follow-up. The significance of positive lymph nodes and the necessity for completion right hemicolectomy remain unclear. Highlights: Appendiceal NETs have a very good prognosis. The prognostic impact of positive lymph is uncertain. Recurrence is rare and occurs decades later mandating selective surveillance and follow-up. The necessity for completion right hemicolectomy remain unclear.